2016
DOI: 10.1002/ange.201608526
|View full text |Cite
|
Sign up to set email alerts
|

A Cascade Strategy Enables a Total Synthesis of (±)‐Morphine

Abstract: Morphine has been at arget for synthetic chemists since Robinson proposed its correct structure in 1925, resulting in al arge number of total syntheses of morphine alkaloids. Here we report atotal synthesis of (AE)-morphine that employs two key strategic cyclizations:1 )ad iastereoselective lightmediated cyclization of an O-arylated butyrolactone to form atricyclic cis-fused benzofuran and 2) acascade ene-yne-ene ring closing metathesis to forge the tetracyclic morphine core. This approach enables as hort and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…Finally, (‒)-codeine was readily converted to (‒)-morphine ( 1a ) by demethylation with boron tribromide 54 in 81% yield. The spectra data of synthetic (‒)-morphine and (‒)-codeine are consistent with the reported ones from literatures 7,8 .
Fig. 5Asymmetric total synthesis of (‒)-codeine ( 1b ) and (‒)-morphine ( 1a ).
…”
Section: Resultssupporting
confidence: 88%
“…Finally, (‒)-codeine was readily converted to (‒)-morphine ( 1a ) by demethylation with boron tribromide 54 in 81% yield. The spectra data of synthetic (‒)-morphine and (‒)-codeine are consistent with the reported ones from literatures 7,8 .
Fig. 5Asymmetric total synthesis of (‒)-codeine ( 1b ) and (‒)-morphine ( 1a ).
…”
Section: Resultssupporting
confidence: 88%
“…A survey of different palladium catalysts (see SI) revealed that the commercially available Pd-complex containing PPh t Bu 2 (without addition of external ligand) afforded improved results (79% yield with 18a, entry 12; 85% yield with 18b, entry 13). Furthermore, bases with potassium cation proved important to maintain the reaction yields (entries [13][14][15][16] and the use of t BuOK allowed for an 89% isolated yield of 17b with complete conversion of 18b (entry 17). Reducing the loading of t BuOK from 2.0 to 1.4 equiv.…”
Section: L8mentioning
confidence: 99%
“…Second, synthetic biologists have recently achieved the complete biosynthesis of thebaine and derivatives in yeast, which, however, is far from practical application. Moreover, synthetic chemists have developed over 30 total syntheses of morphine and congeners, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] but none of these de novo approaches, especially those to oxycodone (3) [18][19][20][21][22] and related derivatives 4-7, are competitive in cost with the current farming/isolation/semisynthesis protocol. An important solution to the practical synthesis of opioids would be to mimic the methods employed by the Mother Nature.…”
Section: Introductionmentioning
confidence: 99%
“…Morphine: 2016 A voltammetric sensor for determination of paracetamol in the presence of morphine [ 313 ]; a short cascade strategy for the stereoselective synthesis of morphine [ 314 ]; extraction of morphine from poppy seeds [ 315 ]; HPLC method for the simultaneous determination of morphine sulfate and naltrexone hydrochloride content in bulk, solid dosage forms [ 316 ]; life cycle assessment from opium poppy farming to the packaging of morphine [ 317 ]; LC-HRMS for the characterization of transformation products and comparison between irradiated samples and those that have not been irradiated [ 318 ]; determination of Morphine in pharmaceutical products by on-line SPE-HPLC [ 319 ]; 2017 solid state vibrational spectroscopic properties of morphine sulfate pentahydrate studied using FTIR-ATR [ 320 ]; review of the research progress on the synthesis of Morphine alkaloids [ 321 ]; Impurity profiling of morphine by LC-HESI-MS [ 322 ]; design and synthesis of carboxylic group functionalized hollow microporous organic capsules for encapsulation of morphine for prolonged release [ 323 ]; characterization of Morphine, Morphine Hydrochloride, and their Hydrates using 1-dimensional and 2-dimensional solid-state NMR and complemented with powder X-ray diffraction, FTIR, and Raman [ 324 ]; one-pot multicomponent approach to synthesize a new series of morphine derivatives [ 325 ]; high-performance thin-layer chromatography-densitometry method for the quantitative analysis of morphine in the tablets of the Ayurvedic medicines [ 326 ]; tandem Brook rearrangement/silicon Polonovski reaction/fragmentation to give formamide derivatives in moderate yields [ 327 ]; asymmetric total synthesis of (−)-morphine [ 328 ]; stability studies of opioid analgesic, morphine-6-O-sulfate in various buffers and biological matrices and analyzed by HPLC-DAD analysis [ 329 ]; Quantum dots (QDs)-labeled antibody fluorescence immunoassays (FLISA) for the rapid detection of morphine for on-site screening of poppy shell added illegally in hot pot soup base [ 330 ]; rapid construction of the 6/6/5 tricyclic framework via a tandem radical cyclization reaction [ 331 ]; Arymo ER - a new abuse deterrent Morphine formulation [ 332 ]; ALERRT((R)) to quantitative measure the effort required to compromise prescription opioid abuse-deterrent tablets [ 333 ]; comparison of the abuse potential of intact and manipulated morphine abuse-deterrent, extended-release injection-molded tablets (morphine-ADER-IMT) with morphine sulfate ER tablets [ 334 ]; compare abuse potential after insufflation of manipulated morphine abuse-deterrent, extended-release injection-molded tablets (morphine-ADER-IMT) with that of marketed morphine ER tablets [ 335 ]; synthesis of morphinans using a programmed serial stereochemical relay […”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%